Obstinate Hebrews : representations of Jews in France, 1715-1815 - Schechter, Ronald (University of California Press, 2003)
Enlightenment writers, revolutionaries, and even Napoleon discussed and wrote about France's tiny Jewish population at great length. Why was there so much thinking about Jews when they were a minority of less than one percent and had little economic and virtually no political power? In this unusually wide-ranging study of representations of Jews in eighteenth-century France--both by Gentiles and Jews themselves--Ronald Schechteroffers fresh perspectives on the Enlightenment and French Revolution, on Jewish history, and on the nature of racism and intolerance. Informed by the latest historical scholarship and by the insights of cultural theory, Obstinate Hebrews is a fascinating tale of cultural appropriation cast in the light of modern society's preoccupation with the "other." Schechter argues that the French paid attention to the Jews because thinking about the Jews helped them reflect on general issues of the day. These included the role of tradition in religion, the perfectibility of human nature, national identity, and the nature of citizenship. In a conclusion comparing and contrasting the "Jewish question" in France with discourses about women, blacks, and Native Americans, Schechter provocatively widens his inquiry, calling for a more historically precise approach to these important questions of difference
Keywords: Napoleon -- I, -- Emperor of the French, -- 1769-1821 -- Relations with Jews.; Napoleon -- I, -- Emperor of the French, -- 1769-1821; Jews -- France -- Identity.; Jews -- Public opinion.; Public opinion -- France -- History -- 18th century.; Public opinion -- France -- History -- 19th century.; Jews in literature.; French literature -- 19th century -- History and criticism.; France -- Ethnic relations.; Jews -- France -- Social conditions -- 18th century.; Juifs -- France -- Identité.; Juifs -- Opinion publique.; Opinion publique -- France -- Histoire -- 18e siècle.; Opinion publique -- France -- Histoire -- 19e siècle.; Juifs dans la littérature.; Littérature française -- 19e siècle -- Histoire et critique.; Juifs -- France -- Conditions sociales -- 18e siècle.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; HISTORY -- Europe -- General.; Ethnic relations; French literature; Jews -- Identity; Jews in literature; Jews -- Public opinion; Jews -- Social conditions; Public opinion; Relations with Jews; France; 1700-1899; acculturation.; alienation.; antisemitism.; assimilation.; belonging.; citizenship.; cultural appropriation.; cultural theory.; discrimination.; enlightenment.; europe.; exile.; feminism.; france.; french history.; french jews.; french revolution.; gender.; homeland.; human nature.; indigenous people.; intolerance.; jewish history.; jewish population.; judaica.; judaism.; national identity.; native americans.; nonfiction.; othering.; politics.; prejudice.; racism.; religion.; religious difference.; social body.; social issues.; tradition.; Criticism, interpretation, etc.; History